Toxoplasmosis and Iron Chelation in Toxoplasma Infection; Overview (Journal of Pharmaceutical Negative Results, 2023)
Background: Toxoplasma gondii was initially discovered by accident, in 1908, by a scientist, Charles Nicolle, who was searching for a reservoir of Leishmania in a native rodent, Ctenodactylus gundi in Tunis. T. gondii is acoccidian parasite with cats is the definitive host, and warm-blooded animals including human as intermediate hosts. Prevalence of pregnant women exposed to T. gondii in European countries was measured by serological porcedures, with seroprevalence values ranging from 9 to 67%.Latent toxoplasmosis is wide spread in pregnant women especially in some low and middle income countries of Africa and South America. So, there is a need for improved prevention and control efforts to reduce the health risks to women and newborns. The differences in prevalence rates in the worldwide population may be associated with various factors related to each region/country and specific characteristics of the population as well with the diagnostic methods used. Isolation of T. gondii from blood or body fluids establishes that the infection is acute. Attempts at isolation of the parasite can be performed by mouse inoculation or inoculation in tissue cell cultures of virtually any human tissue or body fluid. Demonstration of tachyzoites in tissue sections or smears of body fluid (e.g., cerebro spinal fluid (CSF) or amniotic fluids) establishes the diagnosis of the acute infection. Immunological methods were the preferred and most common diagnostic method for diagnosis of toxoplasmosis in clinical laboratories in past century. These methods are based on recognition of T. gondii surface antigens by host T. gondii-specifc immunoglobulins. Despite the significant improvement in serological methods, there are still unresolvable limitations such as inability of these methods to confrm the presence of parasite in fetus and brain in congenital transmission and/or immunocompromised patients. Development of the molecular methods induced a great revolution in the diagnosis of infectious diseases in general. To overcome the limitations of the serological tests, diferent molecular methods including polymerase chain reaction(PCR), nested PCR, real-time PCR(RT-PCR) and also loop-mediated isothermal amplifcation (LAMP) techniques have been developed to detect T. gondii DNA in biological samples. Treatment of toxoplasmosis varies according to the type and severity of the infection. For pregnant women and immunocompromised patients, the use of sulfadiazine and pyrimethamine is not recommended because it generates serious side effects. Passive immunization with monoclonal Abs in toxoplasmosis has been revitalized. It was shown that the transfer of human monoclonal Ab Fab fragments specific to the T. gondii surface antigen 1 (SAG1) protein into mice significantly improved survival rates.